EKSPLORASI NILAI-NILAI SOSIAL DALAM SASTRA LISAN MASYARAKAT DONGGO KABUPATEN BIMA - Abimanyu, Dwi Yanto; Ikra, Ikra; Haris, A. (STKIP Harapan Bima, 2024)
This study aims to explore the social values embedded in the oral literature of the Donggo community, Bima Regency. The underlying issue of this research is the limited number of studies on how oral literature functions as a medium for transmitting social values within the Donggo indigenous community. Using a qualitative approach, this research employs a descriptive-analytical method with data collected through in-depth interviews and participatory observation. The data were thematically analyzed to identify key social values contained in the oral narratives. The findings indicate that Donggo oral literature is rich in social values, with cooperation, wise leadership, and social harmony emerging as dominant themes. The value of cooperation is reflected in 32% of the analyzed stories, while leadership and social harmony appeared in 24% and 20% respectively. These findings demonstrate that oral literature plays a crucial role in reinforcing social solidarity and maintaining order within the community. This study concludes that Donggo oral literature serves not only as entertainment but also as an instrument for preserving socially relevant values in the lives of the people. The results of this study can serve as a foundation for the preservation of oral traditions and the development of character education based on local culture.